A French Educational Meritocracy in Independent Morocco?. Issue 2 (1st June 2020) - Viguier, Frédéric
Abstract: Since independence in 1956, Morocco has actively promoted Arabic and Arab culture through successive waves of "Arabization" policies in its educational system. Yet, French educational diplomas continue to be crucial resources in Morocco, while national Moroccan degrees retain little social and economic currency. Relying on ethnographic fieldwork in Morocco carried out in 2018, this article looks at students from various socioeconomic backgrounds, asks how the grip of French education seventy years after Moroccan independence is experienced on the ground, and provides historical context to account for this situation. It argues that Morocco is an extreme but representative example of how former French colonies—and countries in the Global South—have created new forms of dependence due to their attempts to expand access to education on limited budgets.